2020
DOI: 10.1523/jneurosci.1975-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Effect of Transient Synchrony States on Motor Performance in Parkinson's Disease

Abstract: Bursts of beta frequency band activity in the basal ganglia of patients with Parkinson's disease (PD) are associated with impaired motor performance. Here we test in human adults whether small variations in the timing of movement relative to beta bursts have a critical effect on movement velocity and whether the cumulative effects of multiple beta bursts, both locally and across networks, matter. We recorded local field potentials from the subthalamic nucleus (STN) in 15 PD patients of both genders OFF-medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…Such movement-related beta power reduction has been suggested to reflect changes in the probability of beta bursts rather than a smooth modulation of sustained beta activity (Feingold et al, 2015), and more recently, it has been emphasized that the beta bursts in the cortical-basal ganglia motor network predict sensorimotor behavior (Feingold et al, 2015;Sherman et al, 2016;Shin et al, 2017;Torrecillos et al, 2018;Little et al, 2019;Wessel 2019) and correlate with motor impairment in patients with Parkinson's disease (Tinkhauser et al, 2017a, b). Indeed, beta bursts in the subthalamic nucleus, a key relay in basal ganglia-cortical circuits, are more predictive of motor impairment than average beta power in patients with Parkinson's disease (Torrecillos et al, 2018;Tinkhauser et al, 2020), and similar observations have been made regarding cortical beta bursts and trialaveraged beta power. Little et al (2019) showed that the timing of beta bursts was a stronger predictor of single trial behaviour than single trial-averaged beta amplitude.…”
Section: Is Beta Bursts or Average Beta Power Related To Motor Performentioning
confidence: 56%
“…Such movement-related beta power reduction has been suggested to reflect changes in the probability of beta bursts rather than a smooth modulation of sustained beta activity (Feingold et al, 2015), and more recently, it has been emphasized that the beta bursts in the cortical-basal ganglia motor network predict sensorimotor behavior (Feingold et al, 2015;Sherman et al, 2016;Shin et al, 2017;Torrecillos et al, 2018;Little et al, 2019;Wessel 2019) and correlate with motor impairment in patients with Parkinson's disease (Tinkhauser et al, 2017a, b). Indeed, beta bursts in the subthalamic nucleus, a key relay in basal ganglia-cortical circuits, are more predictive of motor impairment than average beta power in patients with Parkinson's disease (Torrecillos et al, 2018;Tinkhauser et al, 2020), and similar observations have been made regarding cortical beta bursts and trialaveraged beta power. Little et al (2019) showed that the timing of beta bursts was a stronger predictor of single trial behaviour than single trial-averaged beta amplitude.…”
Section: Is Beta Bursts or Average Beta Power Related To Motor Performentioning
confidence: 56%
“…Specifically, the rapid response of beta activity to the onset and offset of stimulation means that it can be used to target beta bursts in the STN ( Little et al, 2013 , Little et al, 2016b , Little et al, 2016a ; Tinkhauser et al, 2017a ; Velisar et al, 2019 ). These are increasingly reported to play a key role in the mechanism of bradykinesia and rigidity in PD ( Deffains et al, 2018 ; Tinkhauser et al, 2020 , Tinkhauser et al, 2017a , Tinkhauser et al, 2017b ; Torrecillos et al, 2018 ). The ERNA does not provide direct feedback relevant to beta bursts and undergoes relatively slow changes with respect to the duration of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of pathological burst occurrence in the model was a simplified representation of beta burst activity observed in PD. Research has observed that the probability of pathological burst occurrence is modulated in PD patients by factors such as medication and motor tasks (Tinkhauser et al, 2017a(Tinkhauser et al, , 2020. Although not considered in this study, future studies may incorporate modulation of the burst probabilities to emulate variations in burst probabilities induced by these factors.…”
Section: Beta-band Lfp Activitymentioning
confidence: 98%